2015
DOI: 10.1186/s12917-015-0611-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of corticosteroids and their combinations with hyaluronanon on the biochemical properties of porcine cartilage explants

Abstract: BackgroundIntra-articular injection of corticosteroids is used to treat the inflammatory pain of arthritis and osteoarthritis (OA), but our previous study found a deleterious effect of these steroids on chondrocyte cells. Hyaluronic acid (HA) injection has been suggested as a means to counteract negative side effects through replenishment of synovial fluid that can decrease pain in affected joints. To better understand the effects of corticosteroids on these processes, dexamethasone (Dex) and prednisolone (Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 55 publications
2
10
0
Order By: Relevance
“…However, in this study, it was found that the combination treatment with CAR with HA (Comb24 and Comb48) did not decrease chondrotoxicity (and did not increase chondrocyte viability). Similar to our previous study involving OA chondrocyte cultures, co-treatment with HA did not decrease chondrotoxicity caused by CAR (Euppayo et al, 2015), triamcinolone acetonide (Euppayo et al, 2016), dexamethasone (Siengdee et al, 2015) and prednisolone (Siengdee et al, 2015). However, some studies have shown that HA could reduce cytotoxicity on chondrocyte viability after cells were exposed to bupivacaine (Onur, Sitron & Dang, 2013), indomethacin (Hashizume & Mihara, 2009), dexamethasone (Hashizume & Mihara, 2009) and celecoxib (Hashizume & Mihara, 2009).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…However, in this study, it was found that the combination treatment with CAR with HA (Comb24 and Comb48) did not decrease chondrotoxicity (and did not increase chondrocyte viability). Similar to our previous study involving OA chondrocyte cultures, co-treatment with HA did not decrease chondrotoxicity caused by CAR (Euppayo et al, 2015), triamcinolone acetonide (Euppayo et al, 2016), dexamethasone (Siengdee et al, 2015) and prednisolone (Siengdee et al, 2015). However, some studies have shown that HA could reduce cytotoxicity on chondrocyte viability after cells were exposed to bupivacaine (Onur, Sitron & Dang, 2013), indomethacin (Hashizume & Mihara, 2009), dexamethasone (Hashizume & Mihara, 2009) and celecoxib (Hashizume & Mihara, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…However, HA could lessen the side effects of fluoroquinolones when treatment was given in conjunction with those other drugs (Siengdee et al, 2016). On the contrary, the therapeutic effects of HA could not mitigate the side effects of carprofen (Euppayo et al, 2015), corticosteroid (Siengdee et al, 2015) and triamcinolone acetonide (Euppayo et al, 2016) when subjects were treated with HA at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, not only pain relief and suppression of inflammation should be addressed, but also cartilage repair. Recent reports have investigated the combined effects of HA and anti-inflammatory drugs (CSs or NSAIDs) [66,67] in order to develop more effective OA treatments. We evaluated the combined effects of HA with low concentrations of Dex and therapeutic concentrations of Dic or Ace on CSE-impaired chondrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there are concerns about reduced chondrocyte production and increasing apoptosis that eventually result in cartilage deterioration. However, no increased risks were reported with this combination, neither from clinical12 nor histological evidence 13…”
Section: Introductionmentioning
confidence: 88%